Video elicited physiological signal dataset considering indoor temperature factors - Wang, Kunxia; Zhao, Zihao; Shen, Xueting; Yamauchi, Takashi (Frontiers in Neuroscience, 2023)
Human emotions change with temperature factors. However, most studies on emotion recognition based on physiological signals ignore the effect of temperature factors. This paper proposes a video elicited physiological signal dataset considering indoor temperature factors (VEPT) to explore the impact of different indoor temperature factors on emotions. The database contains galvanic skin response (GSR) data obtained from 25 subjects at three different indoor temperatures. We selected 25 video clips and 3 temperatures (hot, comfortable, cold) as motivational material. And this paper uses classifications to perform emotion recognition on the physiological signals at the above three temperatures. By comparing the recognition rates of different emotions at three temperatures, it was found that positive emotions were enhanced at comfortable temperatures, while negative emotions were enhanced at hot and cold temperatures. Experimental results show that there is a certain correlation between indoor temperature and physiological emotions.